Hemangioma curative effect of PDL, alexandrite, Er:YAG and CO(2) lasers - Remlová, Eva; Dostálová, Taťjana; Michalusová, Iva; Vránová, Jana; Navrátil, Leoš; Rosina, Jozef (Photomedicine and laser surgery, 2011)
OBJECTIVE: Hemangioma is a mesenchymal benign tumor formed by blood vessels. Anomalies affect up to 10% of children and they are more common in females than in males. The aim of this study was to evaluate hemangioma treatment using four different types of lasers, namely, alexandrite, Er:YAG, CO(2), and pulsed dye laser (PDL). BACKGROUND DATA: The argon laser was the first to be used for dermatological patients, namely, with port wine stains (PWS) in the late 1960s and early 1970s. A variety of different lasers and light sources were useful in the treatment of vascular lesions, e.g., KTP, Nd:YAG, CO(2), PDL, and Er:YAG. METHODS: A group of 869 consecutive patients with hemangioma was retrospectively reviewed. The patients including in our study were divided into four groups according to the type of laser used: Alexandrite laser (n=85, 58 women and 20 men), CO(2) laser (n=78, 58 women and 20 men), Er:YAG laser (n=105, 87 women and 18 men), and PDL laser (n=601, 453 women and 148 men). All patients were treated in one session without anesthesia application. The ablative systems vaporized the tissues until the hemangioma was removed. The non-ablative systems used one shot, which destroyed the hemangioma blood vessels. RESULTS: For the treatment efficacy analysis, the following factors were evaluated: therapeutic effect (yes vs. no), loss of pigment (yes vs. no), and appearance of scar (yes vs. no). From results it was evident that the therapeutic effect of all the lasers except alexandrite was very high; almost 100%. In the CO(2) and the Er:YAG laser groups a high percentage of side effects was also observed. Exposure to these lasers caused loss of pigment and scar formation in many cases. The best therapeutic effect, with only minor side effects, has been achieved with the PDL laser. CONCLUSION: It was confirmed that PDL (595 nm, 1.5 ms, 7 mm, 9 - 11 J/cm(2)) had optimal effect without scars. Er:YAG or CO(2) laser radiation with specific characteristics was also useful for small superficial lesions.
Keywords: výsledek terapie; Hemangioma; Analysis of Variance; Lasers, Solid-State; Male; hemangiom; retrospektivní studie; lasery plynové; Statistics, Nonparametric; neparametrická statistika; lasery pevnolátkové; Adult; Lasers, Dye; laserová terapie; Aged; dospělí; mužské pohlaví; senioři; lasery barvivové; Laser Therapy; Treatment Outcome; Lasers, Gas; lidé; ženské pohlaví; analýza rozptylu; Humans; Retrospective Studies; Female; lidé středního věku; Middle Aged